The Legal Status and Rights Protection of Foreign Workers in Indonesia: A Comparative Analysis between Indonesian and Islamic - Prayitno, Sugeng; Durahman, Dani; Hatta, Muhammad; Rasyid, Laila M (Universitas Islam Negeri Raden Intan Lampung, 2025)
The migration of foreign workers (TKA) is a global phenomenon, not exclusive to Indonesia. Since the prophetic era, the role of foreign workers has been documented. In Indonesia, opposition to foreign workers persists because of the perceived threats to domestic employment. This study aimed to discuss the legal status and protection of foreign workers' rights in Indonesia based on Indonesian and Islamic laws. This study used a juridical-normative approach with a comparative law methodology. The findings revealed that Laws 13 of 2013 and 6 of 2023 acknowledge and protect foreign workers' employment in Indonesia, considering necessity, expertise, competence, and scientific advancements. The employment of foreign workers in Islamic jurisprudence is a novel legal challenge. The legal argument used was the Maslahah mursalah, which considers higher Islamic law principles. Islamic law permits foreign workers' employment, based on universal brotherhood, when benefiting from humanity. The recognition of foreign workers in Indonesia has implications for legally protecting their rights, which are aligned with human rights principles in labor law, including rights to facilities, wages, health care, religious freedom, political participation, and sociocultural engagement